Survival of Sweet Potato Meristems Under Different Cryopreservation Regimens - Shevchenko, Nadiya O.; Ivchenko, Tatiana V.; Mozgovska, Anna V.; ÐœÑ–roshnychenkÐ¾, Tatiana Ðœ.; Bashtan, Nataliya Ðž. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 156